1994
DOI: 10.1182/blood.v84.9.2960.2960
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine therapy with gene-transfected cells: single injection of irradiated granulocyte-macrophage colony-stimulating factor-transduced cells accelerates hematopoietic recovery after cytotoxic chemotherapy in mice

Abstract: Development of cell-based delivery systems that can release therapeutic levels of hematopoietic growth factors into the systemic circulation would facilitate treatment of patients requiring cytokine therapy. In this study, we have investigated the potential of granulocyte- macrophage colony-stimulating factor (GM-CSF)-secreting, irradiated syngeneic murine cells to accelerate hematopoietic recovery after cytotoxic chemotherapy. As a model, CMS-5 fibrosarcoma cells, were transduced with a retroviral vector cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 28 publications
(1 reference statement)
0
1
0
Order By: Relevance
“…Indeed, such cells have been shown to be of great advantage to therapy in animal models. Rosenthal et al demonstrated that granulocyte‐macrophage colony‐stimulating factor‐secreting, irradiated syngenic murine cells accelerate hematopoietic recovery after cytotoxic chemotherapy [12]. Recently, Moullier et al reported that intraperitoneally implanted collagen lattices containing genetically modified autologous fibroblasts show a sustained secretion of human β‐glucuronidase in dogs [13].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, such cells have been shown to be of great advantage to therapy in animal models. Rosenthal et al demonstrated that granulocyte‐macrophage colony‐stimulating factor‐secreting, irradiated syngenic murine cells accelerate hematopoietic recovery after cytotoxic chemotherapy [12]. Recently, Moullier et al reported that intraperitoneally implanted collagen lattices containing genetically modified autologous fibroblasts show a sustained secretion of human β‐glucuronidase in dogs [13].…”
Section: Introductionmentioning
confidence: 99%